Pharmacotherapy of Apnea by Cannabimimetic Enhancement, the PACE Clinical Trial: Effects of Dronabinol in Obstructive Sleep Apnea. Issue 1 (7th November 2017) - Carley, David W; Prasad, Bharati; Reid, Kathryn J; Malkani, Roneil; Attarian, Hryar; Abbott, Sabra M; Vern, Boris; Xie, Hui; Yuan, Chengbo; Zee, Phyllis C
Abstract: Study Objectives: There remains an important and unmet need for fully effective and acceptable treatments in obstructive sleep apnea (OSA). At present, there are no approved drug treatments. Dronabinol has shown promise for OSA pharmacotherapy in a small dose-escalation pilot study. Here, we present initial findings of the Phase II PACE (Pharmacotherapy of Apnea by Cannabimimetic Enhancement) trial, a fully blinded parallel groups, placebo-controlled randomized trial of dronabinol in people with moderate or severe OSA. Methods: By random assignment, 73 adults with moderate or severe OSA received either placebo ( N = 25), 2.5 mg dronabinol ( N = 21), or 10 mg dronabinol ( N = 27) daily, 1 hour before bedtime for up to 6 weeks. Results: At baseline, overall apnea–hypopnea index (AHI) was 25.9 ± 11.3, Epworth Sleepiness Scale (ESS) score was 11.45 ± 3.8, maintenance of wakefulness test (MWT) mean latency was 19.2 ± 11.8 minutes, body mass index was 33.4 ± 5.4 kg/m 2, and age was 53.6 ± 9.0 years. The number and severity of adverse events, and treatment adherence (0.3 ± 0.6 missed doses/week) were equivalent among all treatment groups. Participants receiving 10 mg/day of dronabinol expressed the highest overall satisfaction with treatment ( p = .04). In comparison to placebo, dronabinol dose-dependently reduced AHI by 10.7 ± 4.4 ( p = .02) and 12.9 ± 4.3 ( p = .003) events/hour at doses of 2.5 and 10 mg/day, respectively. Dronabinol at 10 mg/day reduced ESS score by −3.8 ± 0.8 points from baseline ( p < .0001) and by −2.3 ± 1.2 points in comparison to placebo ( p = .05). MWT sleep latencies, gross sleep architecture, and overnight oxygenation parameters were unchanged from baseline in any treatment group. Conclusions: These findings support the therapeutic potential of cannabinoids in people with OSA. In comparison to placebo, dronabinol was associated with lower AHI, improved self-reported sleepiness, and greater overall treatment satisfaction. Larger scale clinical trials will be necessary to clarify the best potential approach(es) to cannabinoid therapy in OSA.